Maternal mortality in Campinas: evolution, under-registration and avoidanc - Cecatti, José Guilherme; Faúndes, Aníbal; Surita, Fernanda Garanhani de Castro (São Paulo Medical Journal, 1999)
CONTEXT: Up until a few years ago, maternal mortality did not merit much attention as a worldwide public health issue. The health and social development indicator almost exclusively used was infant death. OBJECTIVE: To study the number, characteristics, basic causes and avoidance of maternal mortality (MM) among women living in the city of Campinas, which occurred between 1985 and 1991, identified from all death certificates of women aged 10 through 49 years. DESIGN: Retrospective and descriptive population-based study. SETTING: University Referal Center. SAMPLES: All eligible death certificates classified as declared and presumed maternal deaths according to the Laurenti criteria for the cause of death were selected and complementary studies of the clinical records were performed. MAIN MEASURES: Day of the week and place of occurrence of death; period of occurrence; transfer from another hospital; number of days from delivery/abortion to death; blood transfusion; opportunity for transfusion; complications; autopsy; basic cause of death. RESULTS: Initially 39 declared maternal deaths were identified and a total of 62 were confirmed by the end of the study. This corresponds to an under-registration rate of 37.1% and to an MM ratio of 45.5 per 100,000 live births. Around three-fourths of these maternal deaths were due to a direct obstetrical cause and were considered avoidable. CONCLUSION: Maternal mortality still is high in the municipality of Campinas, although lower than the mean estimated for Brazil. The predominance of direct obstetric causes and avoidable deaths reinforces the need for public health interventions directed towards avoiding them.